Analisis Keberlanjutan Pengelolaan Ekosistem Mangrove di Desa Apar Kecamatan Pariaman Utara Sumatera Barat - Simamora, Enny Herawati; Samiaji, Joko; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aims to determine the ecological condition of mangrove ecosystems and to analyze the level of sustainability of mangrove ecosystem management in Apar Village. The data obtained were analyzed using RAP-Mforest. The results obtained are the condition of the mangrove ecosystem is classified as good with very dense criteria. The results of the analysis of the sustainability of mangrove management, namely the ecological dimension of 62.42% (quite sustainable), the social dimension of 71.97% (quite sustainable) and the economic dimension of 11.36% (less sustainable). The strategy that can be done is to conduct counseling to the community about how important mangroves are for the lives of people around the coast. The next researcher further examines the institutional and legal dimensions in order to find out the opportunities and challenges in mangrove ecosystem management.